A framework for multiagent deliberation based on dialectical argumentation - Stankevicius, Alejandro G. (2000)
Simply put, a multiagent system can be seen as a collection of autonomous agents that as a whole are able to accomplish goals beyond the reach of any of its members. Agent interaction is widely acknowledged as the feature that provides this added potential. Since many, if not all, of the attractive agent interactions can be recasted as deliberations, a formalization for this process is being actively seek. Deliberations among agents resembles a dialectical process like the one present in many formalizations of defeasible argumentation. This paper exploits that resemblance by defining a framework for multiagent deliberation based on a particular dialectical process borrowed from a well-established system of defeasible argumentation.